2003
DOI: 10.1080/00016480310000520
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between the Hypothalamic—Pituitary—Adrenal Axis and Behavioural Compensation Following Unilateral Vestibular Deafferentation

Abstract: Vestibular compensation is defined as the process of behavioural recovery that occurs following the loss of sensory input from one or both vestibular labyrinths. The visual and postural instability resulting from the vestibular damage must alter the homeostasis of the subject; however, very little research has been conducted that investigates the interaction between vestibular compensation and the adaptive stress response of the body, i.e. the hypothalamic-pituitary-adrenal (HPA) axis. The aim of this review i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…A number of studies have suggested that the hormone cortisol, a steroid released by the body during times of stress, affects vestibular function and the synaptic and neuronal plasticity involved in vestibular compensation [27][28][29]. This suggests the importance of explanation and education about the condition prior to commencement of active therapy to prevent the physiological effects of stress.…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have suggested that the hormone cortisol, a steroid released by the body during times of stress, affects vestibular function and the synaptic and neuronal plasticity involved in vestibular compensation [27][28][29]. This suggests the importance of explanation and education about the condition prior to commencement of active therapy to prevent the physiological effects of stress.…”
Section: Discussionmentioning
confidence: 96%
“…Alternately altered cognition and the change of genes expression in the hippocampus could reflect changes in the brain-hypothalamic-pituitary-adrenal axis due to the chronic stressful experience, involving a stressor specifically associated to hypergravity (Del Signore et al, 2004). This hypothesis is supported by the existence of a hypothalamic-pituitary-adrenal axis activation induced by vestibular lesions (Gliddon et al, 2003a,b). Gravity changes could also alter cognitive function via modulation of brain vascular reactivity (Porte and Morel, 2011).…”
Section: Effects Of Altered Gravity On the Development Of Gravity Senmentioning
confidence: 90%
“…This was confirmed by modifications of the regulation of corticotrophin-releasing factor and arginine vasopressine in the PVN and the VN ( 56 ). The release of glucocorticoids is known to contribute to the neurochemical mechanisms of vestibular compensation ( 110 ), and agonists and antagonists of the glucocorticoid receptors accelerate and slow postural compensation, respectively ( 111 ).…”
Section: Ten Recommendations For Optimal Functional Recoverymentioning
confidence: 99%